Toxicological effects of fluazuron on bovine reproductive cells: Implications for fertilization, sperm quality, and oviductal integrity - Campagna, Anabella Andrea (2025)
Fil: Campagna, Anabella Andrea. Universidad Nacional de La Plata. Facultad de Ciencias Veterinarias. Argentina